+0  
 
0
172
3
avatar

12[(2/3)*2 ÷ 1/3 - 5/6 × 1/2]

Guest Mar 10, 2017
 #2
avatar+87334 
+5

12[(2/3)^2 ÷ 1/3 - 5/6 × 1/2] =

 

12 [ (4/9 ) ÷ (1/3) - (5/6) * (1/2) ]  =

 

12 [ (4/9) * (3/1) - (5/6) * (1/2) ] =

 

12 [ 12/9  - 5/12] =

 

12 [ (12)(12) - (5)(9) ] / 108  =

 

(12/108) [ 144 - 45] =

 

(1/9) [ 99] =

 

99/9 =

 

11

 

 

cool cool cool

CPhill  Mar 10, 2017
 #3
avatar
0

The way I think you typed it= 12((2/3) x 2 ÷ (1/3) - (5/6) x (1/2))

What the answer would be= (424/9)

12[(2/3)*2÷1/3-5/6x1/3))

12((4/3)/(1/3)-(5/18))

12(4-(5/18))

48-(10/9)

47-(1/9)

46.8888888888..... OR (424/9)

Guest Mar 10, 2017

12 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.